Children with Trans Parents: Parent–Child Relationship Quality and Psychological Well-being. (3rd July 2021) - Imrie, Susan; Zadeh, Sophie; Wylie, Kevan; Golombok, Susan
SYNOPSIS: Objective. Families with trans parents are an increasingly visible family form, yet little is known about parenting and child outcomes in these families. This exploratory study offers the first quantitative assessment of parent–child relationship quality and child socio-emotional and behavioral adjustment in families with a self-identified trans parent with school-aged children. Design. A sample of 35 families (37 trans parents, 13 partners, and 25 children aged 8–18 years) was recruited primarily through social media. Parents, children, and teachers were administered a range of standardized interview and questionnaire assessments of parent–child relationship quality, quality of parenting, psychological adjustment, and gender-related minority stress. Results. Parents and children had good quality relationships, as assessed by both parents and children, and children showed good psychological adjustment. Child age at the time the parent communicated their gender identity to the child was unrelated to child outcomes. Conclusions. Parents and children in trans parent families had good quality relationships and children showed good psychological adjustment. The findings of this exploratory study challenge commonly held concerns about the potentially negative effects on children of growing up with a trans parent.